PENGARUH KETERAMPILAN GURU DALAM MEMBERIKAN PENGUATAN PADA PEMBELAJARAN PAI TERHADAP PARTISIPASI AKTIF PESERTA DIDIK DI SMPN 3 SINJAI UTARA - Desianti, Nurfadillah; Suriyati, Suriyati; Nur, Makmur Jaya (Dahzain Nur, 2023)
This study aims to prove the effect of the teacher's skills in providing reinforcement in PAI learning on the active participation of students at SMPN 3 Sinjai Utara. This research is a quantitative research using a survey approach. Data taken using questionnaires and documents. Data processing uses multiple regression analysis techniques with a significant level of 95% using SPSS 20. This study shows that the skills of teachers in providing reinforcement significantly influence the active participation of students in Islamic Religious Education subjects at SMPN 3 Sinjai. Whereas at a significant value or probability of 0.000 <0.05, the teacher's skills in providing reinforcement have an influence on the active participation of students in Islamic Religious Education subjects at SMPN 3 Sinjai.2). The great influence of the teacher's skills in providing reinforcement to the active participation of students in the subject of Islamic Religious Education at SMPN 3 Sinjai can be seen in the model summary table by looking at R Square = 0.641 or 64.1% so the teacher's skills influence in providing reinforcement to active participation students in the subject of Islamic Religious Education at SMPN 3 Sinjai is 64.1%, the rest is influenced by other factors